Fracture risk, bone density and vitamin D in diabetic women - Lucantonio Debellis; Domenico Basta (Nutrimentum et Curae)
Aging is associated with the increasing prevalence of both type 2 diabetes mellitus and osteoporosis, especially in the elderly and female population.